Electrochemical Sensing of Nitric Oxide on Electrochemically Reduced Graphene-Modified Electrode - Yu-Li Wang; Guang-Chao Zhao (International Journal of Electrochemistry)
Graphene-modified electrode was prepared through electrochemically reducing graphene oxide on the surface of a glassy carbon electrode in PBS solution. The as-prepared electrode owns higher stability and stronger catalytic activity towards the oxidation of nitric oxide (NO). At the electrode, an oxidation peak of NO can be observed at about 1.05 V (versus Ag/AgCl), and the electrode reaction of NO is controlled by diffusion process. Under the optimum conditions, the peak currents are dependent linearly on NO concentrations in the range from 7.2×10−7 to 7.84×10−5 M with a limit of detection of 2.0×10−7 M. The response time of the as-prepared electrode to NO is less than 3 s, and the sensitivity is about 299.1 μA/mM, revealing that the electrode can be used as an excellent sensor for the determination of NO. With further modification of Nafion, the determination is free from the interference of nitrite and some other biological substances. This investigation provides an alternate way for the determination of NO.